Effects of reducing light-curing time of a high-power LED device on shear bond strength of brackets - Almeida, Layene Figueiredo [UNESP]; Martins, Lidia Parsekian [UNESP]; Martins, Renato Parsekian [UNESP] (Urban & Vogel, 2018)
Purpose To assess the effects of reducing the curing time of a high-power light-emitting diode (LED) unit (Valo, Ultradent, South Jordan, UT, USA) on shear bond strength (SBS) of metal brackets and on the amount of adhesive remnant of two orthodontic composites. Methods Eighty human premolars were divided into four groups (G1-4) according to curing time and composite: G1 (Transbond XT, 6s), G2 (Opal Bond MV, 6s), G3 (Transbond XT, 3s), and G4 (Opal Bond MV, 3s). Twenty-four hours after bonding, brackets were subject to a SBS test performed with a universal testing machine. Enamel surface was analyzed by SEM and the amount of adhesive remnant was assessed by the Image J software area calculation tool. Two-way analysis of variance was used for statistical analysis of SBS data, while Friedman and Mann-Whitney post hoc tests were used to analyze data on the amount of adhesive remnant. Results Time and composite significantly affected SBS (p<0.001). The 6s curing showed a higher SBS value (21.56 MPa) in comparison to 3s curing (15.79 MPa). Transbond XT composite showed a significantly higher SBS value (21.06 MPa) compared to Opal Bond MV (16.29 MPa). After the SBS test, Opal Bond MV showed a significantly greater amount of composite adhered to enamel (p<0.001). Conclusion Reducing exposure time from 6 to 3s significantly decreased mean values of SBS, even with the use of a high-power LED unit. Reduction in time did not affect the amount of adhesive remnant.
Keywords: Light curing of dental adhesives; Orthodontic brackets; Dental bonding; Dental enamel; Dental cements